Monitoring voltage fluctuations of intracellular membranes - Rad, Masoud Sepehri; Cohen, Lawrence B.; Braubach, Oliver; Baker, Bradley J. (NATURE PUBLISHING GROUP, 2018)
In eukaryotic cells, the endoplasmic reticulum (ER) is the largest continuous membrane-enclosed network which surrounds a single lumen. Using a new genetically encoded voltage indicator (GEVI), we applied the patch clamp technique to cultured HEK293 cells and neurons and found that there is a very fast electrical interaction between the plasma membrane and internal membrane(s). This discovery suggests a novel mechanism for interaction between the external membrane and internal membranes as well as mechanisms for interactions between the various internal membranes. The ER may transfer electrical signals between the plasma membrane and other internal organelles. The internal membrane optical signal is reversed in polarity but has a time course similar to that of the plasma membrane signal. The optical signal of the GEVI in the plasma membrane is consistent from trial to trial. However, the internal signal decreases in size with repeated trials suggesting that the electrical coupling is degrading and/or the resistance of the internal membrane is decaying.
Keywords: ENDOPLASMIC-RETICULUM; PLASMA-MEMBRANE; FLUORESCENT PROTEIN; CONTACT SITES; ACTION-POTENTIALS; NUCLEAR-ENVELOPE; ER; JUNCTIONS; LYMPHOCYTES; EXPRESSION